Protein Deiminase 4 and CR3 Regulate Aspergillus fumigatus and β-Glucan-Induced Neutrophil Extracellular Trap Formation, but Hyphal Killing Is Dependent Only on CR3 - Clark, Heather L.; Abbondante, Serena; Minns, Martin S.; Greenberg, Elyse N.; Sun, Yan; Pearlman, Eric (Frontiers in Immunology, 2018)
Neutrophil extracellular trap (NET) formation requires chromatin decondensation prior to nuclear swelling and eventual extracellular release of DNA, which occurs together with nuclear and cytoplasmic anti-microbial proteins. A key mediator of chromatin decondensation is protein deiminase 4 (PAD4), which catalyzes histone citrullination. In the current study, we examined the role of PAD4 and NETosis following activation of neutrophils by A. fumigatus hyphal extracts or cell wall β-glucan (curdlan), and found that both induced NET release by human and murine neutrophils. Also, using blocking antibodies to CR3 and Dectin-1 together with CR3-deficient CD18-/- and Dectin-1-/- murine neutrophils, we found that the β-glucan receptor CR3, but not Dectin-1, was required for NET formation. NETosis was also dependent on NADPH oxidase production of reactive oxygen species (ROS). Using an antibody to citrullinated histone 3 (H3Cit) as an indicator of PAD4 activity, we show that β-glucan stimulated NETosis occurs in neutrophils from C57BL/6, but not PAD4-/- mice. Similarly, a small molecule PAD4 inhibitor (GSK484) blocked NET formation by human neutrophils. Despite these observations, the ability of PAD4-/- neutrophils to release calprotectin and kill A. fumigatus hyphae was not significantly different from C57BL/6 neutrophils, whereas CD18-/- neutrophils exhibited an impaired ability to perform both functions. We also detected H3Cit in A. fumigatus infected C57BL/6 corneas, but found no difference between C57BL/6 and PAD4-/- mice in either corneal disease or hyphal killing. Taken together, these findings lead us to conclude that although PAD4 together with CR3 mediated ROS production is required for NET formation in response to A. fumigatus, PAD4 dependent NETosis is not required for A. fumigatus killing either in vitro or during infection.